Keseriusan Pengelolaan Administrasi Materiil di Instansi Pemerintah - Idi Setyo Utomo (The Winners, 2003)
Article discusses one of the source or input needed by organization to achieve their goals, that is contribution. Contribution as country asset need to be organized. Because it is not simple to run the country asset or contribution. The country asset must be well organized so that the government effort on developing country asset must be done simultaneously and it becomes an integral part of national development.